A tale of two distal demonstratives in Dagaare: Reflections on directionality principles in grammaticalisation. (November 2017) - Mwinlaaru, Isaac N.; Yap, Foong Ha
Abstract: For the past half century, the versatile nature of demonstratives across languages has increasingly attracted attention in language typology. The present study contributes to this research agenda by examining the grammaticalisation pathways of two distal demonstratives in the Lobr dialect of Dagaare (Niger-Congo: Gur), namely, nɛ, an adnominal demonstrative, and lɛ, a pronominal demonstrative. The analysis reveals that the adnominal demonstrative nɛ first got reanalysed as an identifying copula verb and, subsequently fused with third person pronouns, ʋ and a, to derive identifying pronouns, nʋ and na respectively. Further, the identifying pronouns nʋ and na fused with the attributive copula ι to derive the focus particle nι. The identifying pronoun na has also been reanalysed into an affirmative final particle. On the other hand, the pronominal demonstrative lɛ first developed into a scalar demonstrative determiner and then into an intensifier. Subsequently, the scalar demonstrative determiner evolved into a copula, which fused with third person pronouns ʋ, a and bɛ to derive the emphatic counterparts of these pronouns, comprising ʋ lɛ, alɛ and bɛ lɛ respectively. These are further cliticised and have evolved into adnominal demonstratives and then postnominal focus particles. These grammaticalisation trajectories contribute to a finer-grained and richer account of the diachrony and typology of demonstratives, including the substantivizing role of morpho-phonemic fusion on the development of grammaticalisation chains. Highlights: A1 – Demonstrative determiner nɛ evolved through identifying copula nɛ, identifying pronouns nʋ and na into focus particle nι. A2 – Identifying pronoun na is also reanalysed as clause final affirmative na. B1 – Demonstrative pronoun lɛ evolved into scalar demonstrative lɛ and then intensifier lɛ. B2 – Scalar demonstrative lɛ evolved into identifying copula lɛ and then partly into emphatic pronouns ʋlɛ, alɛ and bɛlɛ. B3 – Emphatic pronouns ʋlɛ, alɛ and bɛlɛ evolved into demonstratives ʋl, al and bɛl, subsequently reanalysed as postnominal focus markers.